EPPR Progress Report to SAO meeting Fairbanks, March 2016. - Emergency Prevention, Preparedness, and Response (EPPR) (Emergency Prevention, Preparedness and Response (EPPR)., 2015)
Arctic Council working group Emergency Prevention, Preparedness and Response (EPPR)s progress report. Submitted to the Arctic Council's Senior Arctic Officials meeting in Fairbanks, USA, March 16-17, 2016.